Evaluation of the germination of seeds of Capparis spinosa L in laboratory conditions - Sh.M. Ergashev Ph.D. (Zien Journals, 2024)
Fertilization of Capparis spinosa L. seeds was studied in laboratory conditions due to low natural fertility
Keywords: Seeds; germination; drought resistance